Systematic Review on COVID-19 Vaccines: Comparative Study of AstraZeneca, Pfizer-BioNTech, Sputnik V, Johnson & Johnson, Moderna and Corona Vac. - Katawa, Gnatoulma; Tchopba, Christèle Nguepou; Tchadié, Pélagie E.; Simfele, Christelle H.; Kamassa, Eya H.; Amessoudji, Marthe O.; Bara, Fagdéba D.; Ameyapoh, Yaovi; Karou, Simplice D. (International Journal of Innovative Research in Medical Science, 2021)
The novel Coronavirus (SARS-CoV-2) has spread all over the world and the disease, COVID-19, is still wreaking a lot of havoc. Vaccination seems to be the best solution to overcome this pandemic. Several vaccines have been proposed around the world and some of them are already being dispensed, such as AstraZeneca, Pfizer-BioNTech, Sputnik V, Johnson & Johnson, Moderna and CoronaVac. Population around the World have expressed many doubts about these vaccines and resistance to vaccination has been observed. This, for lack of reliable information on these vaccines. The purpose of this systematic review is to provide a comparison of these homologated vaccines and reliable information on them. Online databases were investigated to search publications on these vaccines and the bibliography was created using Endnote 7.0. Investigations concerned antigenic targets, vaccine types, number and timing of doses, neutralizing antibodies, cellular immunity and safety concerns. The main target protein in COVID-19 vaccines is the spike protein (S). Whereas AstraZeneca, Sputnik V and Johnson & Johnson vaccines are adenoviral vector vaccines, Pfizer-BioNTech and Moderna are mRNA vaccines while CoronaVac is a viral attenuated vaccine. Except for Johnson & Johnson which requires one dose, the other vaccines require two doses. All of them induced cellular and humoral immune responses. This review has allowed us to provide to the scientific community and population reliable information about the vaccines and their safety concern.